1998
DOI: 10.1073/pnas.95.16.9500
|View full text |Cite
|
Sign up to set email alerts
|

Zf9, a Kruppel-like transcription factor up-regulated in vivo during early hepatic fibrosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
196
2
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(208 citation statements)
references
References 38 publications
(36 reference statements)
8
196
2
2
Order By: Relevance
“…28 In rat HSC, KLF6 is rapidly induced in response to liver injury and participates in the regulation of genes associated with the fibrogenic phenotype of HSC. 29 Based on these observations, HSP47 expression by HSC might be predicted to be regulated in an activation-dependent manner. The available data do not confirm this prediction and suggest that the transcriptional regulation of HSP47 by HSC may differ from that of 3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 In rat HSC, KLF6 is rapidly induced in response to liver injury and participates in the regulation of genes associated with the fibrogenic phenotype of HSC. 29 Based on these observations, HSP47 expression by HSC might be predicted to be regulated in an activation-dependent manner. The available data do not confirm this prediction and suggest that the transcriptional regulation of HSP47 by HSC may differ from that of 3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of proliferation was determined by assaying 3 H-thymidine incorporation into DNA as described previously. 6 …”
Section: Methodsmentioning
confidence: 99%
“…Krüppel-like factor 6 (KLF6), a ubiquitously expressed zinc finger transcription factor, 6 has been identified as a tumor suppressor gene in prostate, 7,8 colon, 9 and nasopharyngeal 10 cancers, as well as astrocytic gliomas. 11 Moreover, downregulation of KLF6 messenger RNA levels has been described in lung 12,13 and esophageal 14 cancers, the latter also being associated with promoter methylation.…”
mentioning
confidence: 99%
“…We focused our present studies on the Kru Èppel-like zinc ®nger transcription factors (Ruppert et al 1988) which are a subset of the abundantly found DNA-binding C 2 H 2 -type zinc ®nger factors in eukaryotes (Klug & Schwabe 1995). Exempli®ed by the factors Sp1 (Dynan & Tjian 1983) and GBF (Suzuki et al 1998) (also known as CPBP (Koritschoner et al 1997) and Zf9 (Ratziu et al 1998) but hereafter referred to as GBF), they often bind GC-rich sequences with similar sequence-speci®c binding properties (Sogawa et al 1993;T. Suzuki & M. Horikoshi, unpublished results).…”
Section: Introductionmentioning
confidence: 99%